P14.76 Characteristics of anaplastic oligodendrogliomas short-term survivors: a POLA network study. (6th September 2019) - Garnier, L; Dehais, C; Curtit, E; Tabouret, E; Ramirez, C; Vauleon, E; Bourg, V; Boone, M; Figarella-Branger, D; Ducray, F
Abstract: BACKGROUND: Although patients with 1p/19q codeleted anaplastic oligodendrogliomas (AO) usually have a prolonged survival, some patients have a poorer outcome. The aim of the present study was to analyze their characteristics. MATERIAL AND METHODS: The characteristics of AO patients with a survival < 5 years included in the POLA network were analyzed and compared to those of AO patients with a survival > 5 years. RESULTS: In January 2019, among the 519 patients AO patients included in the POLA network, 55 patients were short-term survivors and 146 patients had a survival > 5 years. Among the 55 AO short-term survivors, 44 patients (80%) died from tumor progression and 11 patients (20%) from another cause (suicide n=2, toxicity n=2, intercurrent disease n=6, other n=1). Compared to > 5 years survivors, short-term survivors were older (57 years vs 48 years, p<0.001) and less frequently presented with isolated seizures (9% vs 33%, p=0.0017). They presented with tumors that more frequently involved multiple lobes (66% vs 47%, p=0.03), had a higher rate of nuclear atypia (80% vs 48%, p<0.001), a higher proliferative index (Ki67, 26% vs 18%, p<0.001), a higher level of p53 expression (10.8% vs 3.9% p<0.001), and had a higher rate of chromosomal abnormalities (91% vs 71% p=0.008). Compared to > 5 years survivors, short-term survivors less frequently underwent a surgical resection (64% vs 89% p<0.001) and their initial treatment more frequently consisted in temozolomide chemotherapy alone (41% vs 20% p=0.008). CONCLUSION: AO short-term survivors are associated with distinct clinical, radiological, histological and molecular characteristics at diagnosis.